Qualitative and Quantitative Analysis of Patients' Perceptions of the Patient Portal Experience with OpenNotes - Mishra, Vimal K.; Hoyt, Robert E.; Wolver, Susan E.; Yoshihashi, Ann; Banas, Colin (Applied Clinical Informatics, 2019)
Background Access to medical encounter notes (OpenNotes) is believed to empower patients and improve the quality and safety of care. The impact of such access is not well understood beyond select health care systems and notes from primary care providers.Objectives This article analyzes patients' perceptions about the patient portal experience with access to primary care and specialist's notes and evaluates free-text comments as an improvement opportunity.Materials and Methods Patients at an academic health care system who accessed the patient portal from February 2016 to May 2016 were provided a link to complete a 15-item online survey. Those who had viewed at least one note were asked about patient characteristics, frequency of note access, note usefulness, note understanding, and if any action was taken after accessing the note. Free-text comments were associated with nine questions which were analyzed using qualitative methods.Results A total of 23% (1,487/6,439) of patients who viewed the survey in the portal, participated. Seventy-six percent (1,126/1,487) knew that the notes were available on the portal, and of those, 957 had viewed at least one note to continue the survey. Ninety percent of those were older than 30 years of age, and 90% had some college education. The majority (83%) thought OpenNotes helped them take better care of themselves, without increasing worry (94%) or contacting the physician after reading the note (91%). The qualitative analysis of free-text responses demonstrated multiple positive and negative themes, and they were analyzed for potential improvement opportunities.Conclusion Our survey confirms that patients who choose to access their primary care and specialists' online medical records perceive benefits of OpenNotes. Additionally, the qualitative analysis of comments revealed positive benefits and several potential patient portal improvement opportunities which could inform implementation of OpenNotes at other health systems.
Keywords: OpenNotes; patient portal; personal health record; patient engagement; patient experience; quality improvement; digital health